VOICING THE SUBALTERN: DIVINE INTERVENTION AND FEMINIST EMPOWERMENT IN PRIYA’S SHAKTI THROUGH GRAPHIC NARRATIVES - Falgaroo, Nighat; Qazi, Khursheed Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Priya’s Shakti is a 2014 progressive and ingenious graphic novel by Ram Devineni and Dan Goldman that has half-and-half spiritual power, feminism and activism to grapple with the theme of sexual violence in India. The paper probes into the interchange of mythical voice and empowerment by applying the theory of Gayatri Chakravorty Spivak’s postcolonial feminism. Using the concept of Spivak’s “Subaltern”, the paper examines how Priya, the female protagonist, in the novel metamorphosis from a marginalized voice to an empowered figure through the spiritual power of Goddess Parvati with the help of the tiger. The paper delves into the examination and treatment of women character using the seeable and sayable medium of narration. By employing a mythical voice in the narration, the author cerebrally creates a space for survivors of sexual violence to repossess power with modern feminist discourse. The text also presents the concept of Dues ex machina as a force to combat patriarchal norms and inspire other women.